KOSAKATA PERALATAN TRADISIONAL RUMAH TANGGA DALAM BAHASA DAYAK TAMAMBALOH DI KECAMATAN EMBALOH HULU - Ferdi, Leonardus; Sulissusiawan, Ahadi; Muzammil, Ahmad Rabi?ul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractTraditional household equipment is an ancestral inheritance to his children and grandchildren. People who still use traditional equipment generally still live in remote areas or villages. This study uses two methods, for collecting data used interview methods, records, notes, and documentation. While the data analysis used descriptive method. The data in this study are pictures of traditional household appliances, vocabulary of traditional household equipment, lexical meanings of traditional household equipment, and components of meaning. The source of the data in this study is the informant who is a native of the Dayak Tamambaloh tribe. The technique used in this study is direct technique. Data collection tools used in this study are interview guides, recording devices in the form of tape recorders or other types of recording devices, data cards that have been provided for grouping or recording data obtained. The data consists of vocabulary of basic materials of iron, bamboo, fruit, clay / ceramics, wood, sago shells, pandanus thorns and stems, rattan, animal organs, areca nut fronds, stones, blue leaves, cans and zinc, bark. The researcher managed to collect 63 vocabulary words.Keywords: Dayak Tamambaloh Language, Traditional Equipment, Vocabulary